2018
DOI: 10.1111/bjd.16074
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin: a novel topical agent in the treatment of psoriasis

Abstract: Linked Article: Lin et al. Br J Dermatol 2018; 178:124–131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Indigo Naturalis mainly contains indigo, indirubin, tryptanthrin and other alkaloids, as well as indigo ketone, terpenoids, sitosterol and amino acids [78,79]. Indigo and indirubin are the main components of Indigo Naturalis and are the two important indicators for the quality of Indigo Naturalis in the Chinese Pharmacopoeia [17], and indirubin is generally taken as the major effective constituents of Indigo Naturalis for the treatment of acute promyelocytic leukemia and inflammation and autoimmune diseases such as colitis and psoriasis [21,80,81]. However, we found that neither indigo nor indirubin could alleviate IAV-induced ALI by oral administration (data were shown in Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indigo Naturalis mainly contains indigo, indirubin, tryptanthrin and other alkaloids, as well as indigo ketone, terpenoids, sitosterol and amino acids [78,79]. Indigo and indirubin are the main components of Indigo Naturalis and are the two important indicators for the quality of Indigo Naturalis in the Chinese Pharmacopoeia [17], and indirubin is generally taken as the major effective constituents of Indigo Naturalis for the treatment of acute promyelocytic leukemia and inflammation and autoimmune diseases such as colitis and psoriasis [21,80,81]. However, we found that neither indigo nor indirubin could alleviate IAV-induced ALI by oral administration (data were shown in Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using a refined formulation (Lindioil), a recent report indicated that Lindioil ointment is more effective than vehicle for the treatment of nail psoriasis [10]. Because indirubin, the active component of indigo naturalis, is an effective component of IN, it may be a safe alternative for topical treatment of psoriasis, which is quite different from topical corticosteroids [41]. A double-blind, dosage-controlled trial of indirubin in IN reported that Lindioil ointment with 200 lg/g of indirubin is most effective [42].…”
Section: The Effectiveness Of Indigo Naturalis For Psoriasismentioning
confidence: 99%
“…A double-blind, dosage-controlled trial of indirubin in IN reported that Lindioil ointment with 200 lg/g of indirubin is most effective [42]. Because, according to an RCT, the therapeutic effects of topical treatment vary for psoriatic plaques, topical IN may be an alternative treatment for refractory psoriasis, which functions through a different mechanism of action [41]. Most studies have been performed by Li et al; a multicenter RCT is needed in the near future.…”
Section: The Effectiveness Of Indigo Naturalis For Psoriasismentioning
confidence: 99%
“…Indirubin (IDRB) is a bisindole compound, which is the main active ingredient of Indigo naturalis (Sekhon & Koo, 2018). Traditionally, I. naturalis is a component widely used in traditional Chinese medicine (TCM), for example, Xilei‐san (Tao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%